Kebijakan Pemerintah daerah dan Instrumen Pendukungnya dalam Pengelolaan Hutan di Indonesia Era Otonomi Daerah - Asep Saepudin (Jurnal Paradigma, 2011)
This research intend to analyze sincronization between Indonesia government policy and local government policy on forestry management in otonomy era. Method of this research is qualitative, with focusing on Indonesia and local government policy. This research found that there is no policy sincronization or sustainability of forestry management. It was reflected from difference policy between Indonesia and local government on business license of forest products. This condition is caused by, first, Implementation of decentralization on forestry between Indonesia and local government do not have consensus. Secondly, local government does not has commitment to make good forestry management policy.